INTERFAITH DIALOGUE IN INDONESIA AND LUTHER’S TWO KINGDOMS CONTRIBUTION - Amran Simangunsong (MAHABBAH: Journal of Religion and Education, 2021)
Religious pluralism is a reality that Christianity should face in the light of mission. Christian churches should respect the existence of other flourishing world faiths. Christian churches have been forced to see and understand the encounter of people of different faiths especially in Indonesia. The small churches in the non-Christian lands also have to re-think their attitudes to the majority faiths around them.   As a country that is religiously plural where Muslim is a majority, Indonesian churches have been facing the complexity of religious identity. Sometimes it would cause conflict. Therefore, church and society have taken more attention on interfaith dialogue. Luther’s Two Kingdom Doctrine is necessary to contribute the relation of mission in religious pluralistic context. It gives an emphasis of distinction in Christian task in the world. Therefore, INTERFAITH DIALOGUE is part of mission of the church. It is complimentary to the mission of the church in conjunction with evangelism and social witness.